Identification of drug-related problems and pharmacist′s interventions in asthmatic patients at a private tertiary care facility-Pakistan - Aziz Ullah Khan (Archives of Pharmacy Practice, 2015)
Background: Drug-related problems (DRPs) potentially contribute to morbidity, mortality and financial indicators. There is increasing evidence that participation and interventions of clinical pharmacists in health care have a positive influence on clinical practice. Objectives: The main focus of this study was to identify DRPs, evaluate clinical pharmacy services and document pharmacist′s interventions. Materials and Methods: A 3 months prospective observational study from October, 2014 to January, 2015 was carried out on 80 asthmatic patients admitted to pulmonology unit at Northwest general hospital and research center, Peshawar, Pakistan. The drug therapy details of the patients were collected from inpatient treatment charts using a predesigned questionnaire. The DRPs were identified, and clinical interventions made by pharmacists were documented. Results: A total of 37 patients (61.25%) presenting 91 DRPs were identified, including potential drug-drug interactions 39 (48.75%), drug selection 27 (33.75%), drug use process 12 (15%), drug monitoring 5 (6.25%), adverse drug reactions 5 (6.25%) and dosing 3 (3.75%). Clinical interventions documented by pharmacist were drug information response 21 (26.25%), patient education and counseling 14 (17.5%), change/clarify medication order 11 (13.5%), proper storage and cost effectiveness 10 (12.5%), medication error/brand duplication 7 (8.75%), change of drug/dosage 3 (3.75%), dose calculation in special population 3 (3.75%) and discharge plan 2 (2.5%). Of 91 interventions, the pharmacists contacted the consultants for 24 (30%) interventions, postgraduate medical officers/registrars 34 (42.5%), nursing staff 21 (26.25%) and the patients/attendant 12 (15%). 15 (18.75%) interventions were approved by concerned prescribers. Conclusion: To minimize the risks of DRPs and prevent their occurrence, drug therapy requires pharmacist′s timely and effective interventions at all levels.